Radioulnar joint reconstruction: a novel surgical technique and biomechanical assessment for chronic instability - Ferreira, Gustavo Pacheco Martins (J Exp Orthop, 2020)
PURPOSE: This study aims to describe and biomechanically evaluate a novel technique using a strip of the flexor carpi ulnaris tendon for distal radioulnar joint reconstruction. METHODS: Surgical technique was thoroughly detailed, and a cadaveric biomechanical test was conducted to evaluate sagittal plane stability. Pronosupination range of motion was measured before and after the procedure. Dorsal and volar translation resistances were checked in three situations: with the uninjured triangular fibrocartilage complex, after its complete resection and after the surgical procedure. RESULTS: For distal radioulnar joint translation, higher values were found both in dorsal and volar translation in situations with an injured triangular fibrocartilage complex, with means equal to 25.4 mm (SD: 9.4 mm) and 26.1 mm (SD: 8.0 mm), respectively. For intact triangular fibrocartilage complex, both dorsal and volar translations averages were 3.4 mm (SD: 0.9 mm) and 4.5 mm (SD: 1.8 mm), respectively. Finally, when evaluating dorsal and volar translations after surgical reconstruction, means were 6.3 mm (SD: 1.3 mm) and 6.8 mm (SD: 0.9 mm), respectively. Regarding supination and pronation range of motion, which ranged from 57.9 to 63.4(o), there were no differences in mean and median measures, when the cadavers with intact and reconstructed triangular fibrocartilage complex were compared (p > 0.05). CONCLUSION: Promising mechanical evaluations encourage us to hypothesize that the technique effectively reconstructs the dorsal and volar radioulnar ligaments, preserving pronosupination and maintaining the physiological characteristics of the wrist joint. Clinical comparative studies are still necessary to fully validate this procedure. LEVEL OF EVIDENCE: Therapeutic - Level V.